Uji Potensi Fungi Pelapuk Putih Asal Batang Kayu Pinus (Pinus merkusii Jungh et de vriese) Sebagai Pendegradasi Lignin (Test of potential White Rot Fungi at Rotten Pine Wood (Pinus merkusii Jungh et de vriese ) as degrading lignin) - Parlin Bastian Simanjuntak; Edy Batara Mulya Siregar; Nelly Anna (Program studi Kehutanan USU, 2015)
Lignin is a natural compound of plant that has a function for plant cell wall constituent. In pulp industries, lignin is a compound which is hard to be degradad. The purpose of this research is to get white rot fungi in the rotten pine wood, to determine potential of white rot fungi in biopulping process which obtained by measuring the activity of enzyme Lignin Peroxidase (LiP) at white rot fumgi which is obtain from the rotten pine wood. The sample of the rotten pine wood taken from Taman Hutan Raya (Tahura) Berastagi. Bavendamm and ligninolitic enzyme activities test have found three spesies fungi which are in genus Trametes sp.1, Trametes sp.2, and Phanerochaete sp. The highest activity of enzyme lignin peroxidase was produced by Trametes sp.1 fungi by the value is 1,541 U/ml. Key word: White rot fungi, Pine wood, Bavendamm test, enzyme lignin peroxidase.